Metode Bercerita dalam Meningkatkan Kecerdasan Spiritual Siswa pada Pendidikan Agama Kristen - Elsiani, Nina; Tanyid, Maidiantius (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
This study aims to analyze the implementation of pedagogical approach through storytelling method in Christian Religious Education learning, which aims to improve students' spiritual intelligence. The research method used was a qualitative. The results of this study can be summarized as follows: Implementation of pedagogical practices. Using stories related to students' daily situations and combined with initial interaction through prayer and preparation of teaching materials. Effectiveness of using stories: This method is effective in improving students' spiritual intelligence. The stories told make it easier for students to understand and apply spiritual values such as honesty, love and forgiveness. Continuous evaluation: This evaluation is conducted to see changes in behavior, attitudes, and the application of moral and spiritual values in students' lives.